Urinary metabolomic markers of aminoglycoside nephrotoxicity in newborn rats - Hanna, Mina H.; Schaefer, Franz (Pediatric research, 2013)
Aminoglycoside exposure is a common cause of acute kidney injury (AKI). Delay in the diagnosis of AKI using conventional biomarkers has been one of the important obstacles in applying early effective interventions. We tested the hypothesis that urinary metabolomics could identify novel early biomarkers for toxic renal injury.